2014
DOI: 10.1007/s00701-014-2200-z
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of shunt dependency after aneurysmal subarachnoid hemorrhage: results of a single-center clinical trial

Abstract: In this cohort of patients with clinical grade aSAH at admission, larger amounts of subarachnoid blood and large ventricular size on preoperative cerebral CT, and CSF drainage in excess of 1,500 ml during the 1st week after the ictus were significant predictors of shunt dependency. Shunt dependency did not hamper outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 42 publications
4
30
0
Order By: Relevance
“…Early shunt operation performed ≤30 days after SAH onset, which was earlier than the standard period, and late shunt operation >40 days after onset, which was later than the standard period, were used in this study. Previously reported mean intervals between onset of SAH and shunt operation were 17-18 days in two studies 23,26 and 36-45 days in five studies, 4,7,10,12,30 which were compatible with the present study.…”
Section: Modality Of Aneurysm Repair and Timing Of Shunt Operationsupporting
confidence: 93%
“…Early shunt operation performed ≤30 days after SAH onset, which was earlier than the standard period, and late shunt operation >40 days after onset, which was later than the standard period, were used in this study. Previously reported mean intervals between onset of SAH and shunt operation were 17-18 days in two studies 23,26 and 36-45 days in five studies, 4,7,10,12,30 which were compatible with the present study.…”
Section: Modality Of Aneurysm Repair and Timing Of Shunt Operationsupporting
confidence: 93%
“…Since it involves ventricular dilation anatomically, its recognition is primarily based on radiographic techniques, especially CT scans (Figure 4). The bicaudate index (BCI) and relative bicaudate index (RBCI) (calculated, resp., in different age groups) have been commonly accepted and widely applied as the diagnostic measurements since the study of Gijn and colleagues in 1980s (as shown in Figure 5) [17, 2528]. And peers draw a conclusion that if not detected promptly before RBCI > 1.6, the effort to launch a drainage surgery could be in vain because of unimproved outcomes [29].…”
Section: Diagnosismentioning
confidence: 99%
“…Patients with acute course of HCP, in-hospital complications, IVH, high Hunt and Hess Scale score (or low initial Glasgow Coma Scale or high Fisher score), rehemorrhage, posterior circulation location of ruptured aneurysm, and age ≥ 60 have been reported to be at a higher risk of shunt-dependency [35]. Other research reported similarly higher risk of HCP with posterior circulation aneurysm, IVH, greater hemorrhage volume, and older age [4, 5, 28, 36]. Dependency on factors like economy, medical development, and methods to cope with ruptured aneurysms also leads to deferent incidences of shunt-dependent HCP [5].…”
Section: Predictive Factorsmentioning
confidence: 99%
“…Acute PHH requiring a temporary external CSF diversion occurs in 15%–87% of SAH patients . However, not all SAH individuals who suffer from acute PHH require a permanent CSF diversion.…”
Section: Introductionmentioning
confidence: 99%